Influence of salt on drying performance of silver jewfish (Otolithes argentatus) in a Hohenheim type solar tunnel dryer (Journal of the Bangladesh Agricultural University, 2014)
Studies were conducted to investigate the influence of salt treatment on the drying performance of commercially important marine fish, silver jewfish (Otolithes argentatus) in a Hohenheim-type solar tunnel dryer. Different brine concentrations viz., 0%, 10%, 15%, 20% and 25% were used, where fish were treated for 12 hr after sorting, grading, dressing and washing. Temperature inside the dryer varied from 36 to 55ºC with an average air velocity of 1.5 m/s. Moisture content of fish was reduced to 16% and it was found that the use of salt in silver jewfish significantly reduced the drying period in solar tunnel dryer to 34 hr compared to those of 40 hr for control fish. Moisture content of 10% salt treated sample decreased rapidly compared to other salt treated samples where moisture content reduced to below 16% within 34 hr. This indicates that addition of salt in raw material reduced drying time as well as improves the quality of the final product. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21416 J. Bangladesh Agril. Univ. 12(1): 227-233, June 2014